2013
DOI: 10.1057/eps.2013.13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Model United Nations: Diplomatic Simulation as Assessed Undergraduate Coursework

Abstract: Increasingly, simulation-based teaching and learning is finding a place within politics and international relations (IR) programmes. The majority of literature on this style of teaching and learning has positioned it as both an aid to content delivery and as a response to the many challenges facing contemporary higher education. Little guidance is given, however, to the practical considerations of using simulations as a component of assessment or as informing assessed tasks. This article draws upon the experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…One of the key benefits of MUNs is that different students learn in different ways and MUNs add diversity to teaching methods (Obendorf & Randerson, 2013;Shellman & Turan, 2006). By effectively assimilating a SNS into the subject, it had increased capacity to respond to diverse learning styles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key benefits of MUNs is that different students learn in different ways and MUNs add diversity to teaching methods (Obendorf & Randerson, 2013;Shellman & Turan, 2006). By effectively assimilating a SNS into the subject, it had increased capacity to respond to diverse learning styles.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to negotiate, strategise, and form alliances are crucial skills for building resolutions on contemporary issues. MUNs and simulations, offer a particularly good setting for students to develop these skills through the ability to work towards an outcome in a structured, multilateral, and hands on way (Crossley-Frolick, 2014;Obendorf & Randerson, 2013;Shellman & Turan, 2006;Taylor, 2014).…”
Section: Impact Of the Change In Platform On The Nature Of Student Inmentioning
confidence: 99%
“…For example, with regard to teaching international relations, Simpson and Kaussler (2009) found that simulations contribute to the development of key communication and analytical skills. There has also been a long history of Model UN simulations, which can provide students with key vocational skills (Obendorf & Randerson, 2013). Similarly, for law students, moot courts are a well-established simulation exercise to develop oral and written skills, 'to be successful not only in cases brought before their home courts, but in front of international tribunals and other organs' (Grossman, Martin, Rodriǵuez Pinzón, 2008).…”
Section: Human Rights Skills and Simulationsmentioning
confidence: 99%
“…Secondly, a slightly different focus can be found in those contributions focusing primarily on simulation outcomes and learning effects, as well as the evaluation and assessment of simulations (e.g. Obendorf & Randerson 2013;Pettenger, West & Young 2014;Raymond 2010;Shellman & Turan 2006). Thirdly, many publications detail the creation process and concrete application of simulations for taught provision in higher education (Boyer & Smith 2015;Bridge & Radford 2014;Kempston & Thomas 2014;Smith & Boyer 1996;Stover 2007;Tessman 2007).…”
Section: Simulations In the Teaching And Learning Of Irmentioning
confidence: 99%
“…the "security dilemma" (Asal 2005), the predominant focus in the disciplinary literature has been on simulations. These may include simulations of EU organs (Elias 2014;Gusti, Muno & Niemann 2015;Jones & Bursens 2015), the United Nations (Obendorf & Randerson 2013), as well as hypothetical "realistic" scenarios such as the creation of a new International Human Rights Treaty (Kille 2002) or an AIDS conference (Crossley-Frolick 2010). Games have distinct advantages in terms of time management and instructor management, as complexity is reduced by tighter rule structures.…”
Section: Simulations In the Teaching And Learning Of Irmentioning
confidence: 99%